On Traces in Some Analytic Spaces in Bounded Strictly Pseudoconvex Domains. (19th February 2015) - Shamoyan, Romi F.; Mihić, Olivera R.
Abstract : New sharp estimates of traces of Bergman type spaces of analytic functions in bounded strictly pseudoconvex domains are obtained. These are, as far as we know, the first results of this type which are valid for any bounded strictly pseudoconvex domains with smooth boundary.